2010
DOI: 10.1002/anie.200906163
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Lipoteichoic Acid of Streptococcus pneumoniae

Abstract: Mixed signals: The glycophospholipid 1, consisting of two cholinylphospho‐GalNAc units, two 2‐acetamino‐4‐amino‐2,4,6‐trideoxygalactose rings, three glucose residues each with different linkages to other sugar units, and a ribitolphosphate residue, has been synthesized. Target 1 is recognized by the immune system, but not by the TLR‐2 signaling receptor as previously postulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 49 publications
4
37
0
1
Order By: Relevance
“…45 This synthesis is summarized in Scheme 6 and is based on the block coupling of ribitol tetrasaccharide 54 and trisaccharide lipid anchor 55. 45 This synthesis is summarized in Scheme 6 and is based on the block coupling of ribitol tetrasaccharide 54 and trisaccharide lipid anchor 55.…”
Section: Chemical Synthesis Of Tasmentioning
confidence: 99%
“…45 This synthesis is summarized in Scheme 6 and is based on the block coupling of ribitol tetrasaccharide 54 and trisaccharide lipid anchor 55. 45 This synthesis is summarized in Scheme 6 and is based on the block coupling of ribitol tetrasaccharide 54 and trisaccharide lipid anchor 55.…”
Section: Chemical Synthesis Of Tasmentioning
confidence: 99%
“…and Sauvageau et al 15. Total synthesis of a derivative of the more complex LTA from S. pneumoniae has also been achieved16 and its interaction with the host immune system revealed that not TLR‐2 but the complement pathway was activated 17. Since the structural motive is very different between the families of LTAs, and dependent on the origin, a different biological pathway is not a surprise, but what about other LTAs from other Gram‐positive bacteria?…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis was followed by derivatives to find the smallest structure giving activity [15][16][17] and the synthesis of LTA from other bacteria, where S. pneumoniae is a milestone. In this account the synthesis of LTA from S. aureus, 14 S. pneumoniae 18 and Streptococcus sp. DSM 8747 19 ( Figure 2) will be discussed together with their biological activities.…”
Section: Introductionmentioning
confidence: 99%